Effect of Buckwheat (Fagopyrum esculentum) Powder on the Physicochemical and Sensory Properties of Emulsion-type Sausage - Lee, Sol-Hee (Korean J Food Sci Anim Resour, 2018)
Various amounts of buckwheat powder (0%, 1%, 2%, and 3%) were added to emulsion-type pork sausages. The effects of buckwheat powder on the physicochemical characteristics of the emulsion type sausages, including proximate composition, cooking yield, viscosity, pH, instrumental color, texture profile analysis (TPA), and sensory evaluation, were determined. Increased levels of added buckwheat powder led to higher moisture (p<0.05), ash content (p<0.05 or >0.05), and cooking yield (p<0.05). However, the protein and fat contents of the sausage samples were lower (p<0.05) with higher levels of added buckwheat powder. The instrumental color and pH values were affected by the addition of buckwheat powder, which has a pH of 6.1 and associated color coordinates of L*=75.0, a*=1.3, and b*=8.7. Meat batter with 3% buckwheat powder was shown the highest (p<0.05) viscosity indicating great formation of emulsion. There were no significant differences in the TPA among the treated samples. The viscosity value increased with increasing cooking yield in the batter (r(2)=0.7283) i.e. the correlation coefficient between the two measurements was very high and positive. For sensory traits except for tenderness, the highest scores (p<0.05) was detected on sausages with 3% added buckwheat powder by a panel. These results suggest that the addition of 3% buckwheat powder to emulsion-type sausages produces a more beneficial meat product, with a lower fat content, greater formation of emulsion and no adverse effects on sensory properties.